Application of Integrated Project Delivery (IPD) in the Middle East: Implementation and Challenges - Mohamed Sherif; Ibrahim Abotaleb; Fahad K. Alqahtani (Buildings, 2022)
The Integrated Project Delivery method (IPD) is a contractual framework that features enhanced collaboration, risk and reward sharing under a single contract among the major project parties. This delivery method is gaining popularity in the US and other parts of the world, due to its proven results in efficient risk and cost sharing. Despite that, no significant investigations have been made to address the adaptability of the Middle East construction sector to the IPD delivery system. The objective of this research is to investigate the level of preparedness Middle Eastern markets have for adoption of the IPD delivery system. First, a thorough literature review was carried out to identify common barriers and enablers of applying IPD in construction. Second, a survey was carried out to assess and rank such barriers and enablers as they specifically apply to the Middle East construction sector. Third, through structured interviews with contract experts, strategies and guidelines were devised to be used by Middle East owners, consultants, and contractors who have the intention to implement the IPD delivery method in their projects. Finally, a thorough comparison was made between two major Middle Eastern countries, Egypt and the Kingdom of Saudi Arabia (KSA), in terms of IPD application. The findings reveal that the main barriers to implementing IPD stem from cultural resistance to the new system and lack of knowledge about it. The subsequent strategies outlined by the research are expected to help the construction industry in the Middle East gain more depth of knowledge about the benefits and application of IPD.